Pemeriksaan Selaput Dara Dari Perspektif HAM - Sasongko, Purwanto Panji (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Hymen examination is synonymous with the 'virginity test' which is a controversial examination by medical professionals. One of the famous myths about virginity is that 'virginity' is proven by writing the appearance of "intact hymen". Along with the times, this can also have an impact on the legal field, especially health law, that examination of the hymen which is carried out by medical professionals raises pros and cons. The hymen is done by medical professionals properly and correctly when viewed from the perspective of human rights. The form of this research is normative juridical research. with a conceptual approach, while the type of research is descriptive exploratory. Examination of the hymen which can be called a virginity test is not allowed because it is not in accordance with the dignity of women and contains elements of discrimination. This is contrary to Law No. 7 of 1984 (women's convention). While the understanding that is believed to support the elimination of discrimination is the ideology of Feminism, Feminism is an ideology that views differences in women's rights based on the equality of women and men and this is interesting to discuss because of the belief that women experience injustice because of their gender.